The impact of EMU on portfolio management - Martin Brookes (EIB Papers, 1999)
A considerable amount has been written about the impact of EMU on European financial markets. A broad consensus has emerged from this work, with the main conclusions as follows: Government bond markets will be more closely integrated and yields closely correlated. Non-government borrowers will increasingly borrow directly from investors by issuing debt securities rather than borrowing from banks, leading to a US-style corporate bond market. The national bias in equity and fixed income investments will diminish and funds will be increasingly managed against Euro-wide benchmarks, possibly involving some reallocation of existing investments. Equity markets will grow as more companies go public and more investors seek to invest funds in equity markets. There are a raft of additional conclusions which have emerged and some writers make greater claims than others. But the above are the core conclusions of research on EMU and financial markets. This paper is not going to challenge this consensus. Instead it will highlight how EMU will change the behaviour of institutional investors, which is the key factor behind the expected changes to capital markets. It is useful to distinguish between factors influencing the supply of funds in different financial markets and factors influencing the demand for funds. The aggregate approach usually taken often does not make this distinction clear. Most papers look at the size of Euroland financial markets and the barriers to their development caused by having distinct currencies. We aim to ask why EMU is expected to lead investors to change the way that funds are managed, prompting the changes above.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Portfolio-Management; EU-Staaten